Western ethical theories on human nature: an Islamic perspective - Moris, Megawati (s.n, 2012)

(untitled)
The main aim of this research project was to carry out a critical analysis of a Western ethical theory concerning human nature namely, Secular Humanism, from an Islamic perspective. The researcher has examined this modern Western philosophy or life-stance to represent how modern Western civilization conceives and views human nature and how with this conception it tries to solve ethical problems facing contemporary society.